2001
DOI: 10.1002/etc.5620200517
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine remediation in wetland microcosms

Abstract: Laboratory wetland microcosms were used to study treatment of atrazine in irrigation runoff by a field-scale-constructed wetland under controlled conditions. Three experiments, in which 1 ppm atrazine was added to the water column of three wetland, one soil control, and one water control microcosm, were conducted. Atrazine dissipation from the water column and degradate formation (deethylatrazine [DEA]; deisopropylatrazine [DIA]; and hydroxyatrazine [HA]) were monitored. Atrazine dissipation from the water col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 39 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…In mesocosms planted with rice cutgrass [ Leersia oryzoides (L.) Sw.] and broad‐leaf cattails ( Typha latifolia L.), Moore et al (2017) reported greater atrazine removal (51 ± 6.1% and 53 ± 1.9%, respectively) compared with unvegetated controls (28 ± 17%). Runes et al (2001) noted wetland microcosms, via sorption and degradation, were able to reduce atrazine concentrations in the water column. Runes et al (2003) also reported constructed wetlands were able to mitigate 16 to 24% of atrazine associated with nursery irrigation runoff.…”
Section: Resultsmentioning
confidence: 99%
“…In mesocosms planted with rice cutgrass [ Leersia oryzoides (L.) Sw.] and broad‐leaf cattails ( Typha latifolia L.), Moore et al (2017) reported greater atrazine removal (51 ± 6.1% and 53 ± 1.9%, respectively) compared with unvegetated controls (28 ± 17%). Runes et al (2001) noted wetland microcosms, via sorption and degradation, were able to reduce atrazine concentrations in the water column. Runes et al (2003) also reported constructed wetlands were able to mitigate 16 to 24% of atrazine associated with nursery irrigation runoff.…”
Section: Resultsmentioning
confidence: 99%
“…Nominal concentrations of esfenvalerate in test solutions (0.05, 0.1, 0.2, and 0.4 g/L) were verified by gas chromatography/mass spectrometry electron ionization using the method described in Runes et al [19]. In order to obtain sufficient sample for analysis of esfenvalerate at ppt levels, we prepared 33.25 L fortified at concentrations of 0.4, 0.2, and 0.1 g/L esfenvalerate, and 35.25 L at 0.05 g/L esfenvalerate.…”
Section: Chemicalsmentioning
confidence: 99%
“…Nominal concentrations of esfenvalerate in test solutions (0.05, 0.1, 0.2, and 0.4 μg/L) were verified by gas chromatography/mass spectrometry electron ionization using the method described in Runes et al [19]. In order to obtain sufficient sample for analysis of esfenvalerate at ppt levels, we prepared 33.25 L fortified at concentrations of 0.4, 0.2, and 0.1 μg/L esfenvalerate, and 35.25 L at 0.05 μg/L esfenvalerate.…”
Section: Methodsmentioning
confidence: 99%